Matrix analysis - Horn, Roger A.; Johnson, Charles R. (Cambridge Cambridge university press, 1985)
The thoroughly revised and updated second edition of this acclaimed text has several new and expanded sections and more than 1,100 exercises
Keywords: Lineare algebra; Mathematics